TCF7L2 gene associated postprandial triglyceride dysmetabolism- a novel mechanism for diabetes risk among Asian Indians - Madhu, Sri Venkata; Mishra, Brijesh Kumar; Mannar, Velmurugan; Aslam, Mohd; Banerjee, Basudev; Agrawal, Vivek (Frontiers in Endocrinology, 2022)
Aim: TCF7L2 gene is believed to increase the risk of T2DM by its effects on insulin secretion. However, the exact mechanism of this enhanced risk is not clearly known. While TCF7L2 gene has been shown to affect lipid metabolism, these effects have remained largely unexplored in the context of diabetes risk. Methods: Post prandial lipid responses to a standardized fat challenge test were performed in 620 Asian Indian subjects (310 with NGT and 310 with T2DM/prediabetes) and compared between the risk and wild genotypes of the rs7903146 TCF7L2 gene. In 30 subjects scheduled to undergo abdominal surgery (10 each with NGT, Prediabetes and T2DM), adipocyte TCF7L2 gene expression was also performed by real time qPCR and confirmed by protein expression in western blot. Results: T allele of rs7903146 TCF7L2 gene was confirmed as the risk allele for T2DM (OR=1.8(1.2-2.74), p=0.005). TT+CT genotypes of rs7903146 TCF7L2 gene showed significantly higher 4hrTg (p<0.01), TgAUC (p<0.01), peakTg (p<0.01) as well as higher postprandial plasma glucose (p=.006) levels and HOMA-IR (p=0.03) and significantly lower adiponectin levels (p=0.02) as compared to CC genotype. The expression of TCF7L2 gene in VAT was 11-fold higher in prediabetes group as compared to NGT (P<0.01) and 5.7-fold higher in T2DM group as compared to NGT group(P=0.003) and was significantly associated with PPTg and glucose levels. Conclusion: There is significant PPTg dysmetabolism associated with the risk allele of rs7903146 polymorphism as well as adipocyte expression of TCF7L2 gene. Significant upregulation of TCF7L2 gene expression in VAT that correlates with PPTg and glycaemia is also seen in Asian Indians with glucose intolerance. Modulation of PPTg metabolism by TCF7L2 gene and the resultant PPHTg may be a novel mechanism that contributes to its diabetes risk in them.